Temperature and strain-rate dependent mechanical properties of single-layer borophene - Sha, Zhen-Dong (2020)
Borophene, a new two-dimensional (2D) material with metallic characteristic, is promising for use as electrodes and interconnects in flexible nanodevices. Here, we study the mechanical properties of single-layer borophene using molecular dynamics simulations based on a newly developed interatomic potential. It is found that the hexagonal borophene exhibits highly anisotropic mechanical properties. The Young’s modulus and fracture strength in the zigzag direction are much lower than those in the armchair direction. The simulated fracture strength and fracture strain of borophene at 10 K are in good agreement with those predicted by first-principles calculations. We further reveal that the fracture properties of borophene are very sensitive to temperature. When the loading temperature increases from 10 to 700 K, the fracture strength and fracture strain decreases by 50% and 60%, respectively. In contrast, the fracture properties show a relatively weak sensitivity to the strain-rate. When the strain rate changes from 0.00001 to 0.01 ps−1, the fracture strength and fracture strain increase only by 6.8–8.6% and by 11–15%, respectively. Our observations on the temperature and strain-rate dependent fracture strength can be rationalized by the kinetic theory of fracture. The present study provides valuable insights into the deformation and failure behavior of borophene, which are of importance for the design and application of borophene-based nanodevices.